2005
DOI: 10.1007/s00256-005-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary pleomorphic liposarcoma of bone: MRI findings and review of the literature

Abstract: Primary liposarcoma of bone is exceedingly rare. We report a case of primary pleomorphic liposarcoma in the humerus of a 38-year-old female. Radiographs demonstrated an expansile and osteolytic lesion extending from the head to the proximal part of the shaft in the right humerus. MR study showed a defined lesion in the humerus. The lesion had an iso-signal intensity and partial high-intensity lesion on T1-weighted images and a heterogeneous high signal intensity on T2-weighted images. Wide resection and proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Liposarcomas of bone are rare and their MRI appearances include the presence of fat but aggressive features such as bone destruction are usually evident [33,34]. MRI depicts mature fat as intramedullary regions of high T1W SI, high T2W SI greater than subcutaneous fat, and low SI on STIR.…”
Section: Fat Si Within Tumoursmentioning
confidence: 97%
“…Liposarcomas of bone are rare and their MRI appearances include the presence of fat but aggressive features such as bone destruction are usually evident [33,34]. MRI depicts mature fat as intramedullary regions of high T1W SI, high T2W SI greater than subcutaneous fat, and low SI on STIR.…”
Section: Fat Si Within Tumoursmentioning
confidence: 97%
“…Chemotherapy is another treatment modality selected by certain clinicians rather than surgery. Although the first case in 1982 reported the use of chemotherapy as the treatment strategy (5), a total of five cases have been reported (5,6,8,10,12), where combined-treatment chemotherapy was adopted; the survival times for these patients were 10, 16, 70, 7 and 3 months, respectively. In 1999, Rabah et al (8) reported the case of a patient with a liposarcoma of the humerus.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 35 cases have been reported, 9 and only 20 of these fulfilled the criteria for primary liposarcoma of bone, 2 and only 16 had definitive photomicrographs. 3 High-grade soft-tissue liposarcomas do not respond well to treatment (including a combination of surgery and multimodal therapies). Five-year survival rates are <67%, with up to 50% of patients developing local recurrence or metastatic disease within 5 years, 7,17,[30][31][32][33][34] and tumours may recur even 10 years after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Liposarcomas are uncommon tumours of primitive mesenchymal derivation occurring mostly in adults, [1][2][3][4] with an annual incidence of 2.5 per million in the US. They account for 10 to 15% of soft-tissue sarcomas.…”
Section: Discussionmentioning
confidence: 99%